A Study of Factors Affecting Income Inequality in 38 East Java Districts/ Cities in 2012-2015 - Ermatry Hariani (TIJAB (The International Journal of Applied Business), 2019)
Developing economy is very important to fix some of the problems. Each region wants to achieve sustainable economic development. Yet, with the difference of human development index, the open unemployment rate and the districts/ cities minimum wage will form a problem, namely inequality. The purpose of this study is to examine whether the human development index (HDI), the open unemployment rate (TPT) and districts/ cities minimum wage (UMK) had an effect on the income inequality of 38 districts/ cities in East Java in 2012-2015. The methods used in this study is panel data (time series and cross section) of 38 districts/ cities East Java 2012-2015. The model chosen in this study is REM (random effect model) model. The result shows that there is only one significant variable causing income inequality, that is HDI. This means that the high and low of HDI influences the high and low to the income inequality. Meanwhile, two other variables, namely open unemployment rate (TPT) and minimum wage of districts / cities (UMK) have no significant influence to income inequality. In other words, the high-low of TPT and UMK have no influence to the high and low of the income inequality in East Java during the study period.